Pharmacist interventions focus in high impact journals (2007)
ABSTRACT: A significant professional development of pharmacy practice has taken place over recent years. Pharmacists have taken on a challenging new role in patient health care, and accordingly, have assumed the responsibility to ensure the possible best patient outcomes with drug therapy. Several major trends have converged with the shared objective of raising pharmacist’s level of responsibility. The role of the clinical pharmacy1, which is defined as “the area of pharmacy concerned with the science and practice of rational medication for the purpose of ensuring optimal patient outcomes”, was the foundation for the development of the actual philosophy of practice, which consists in adopting a patient-centred pharmaceutical care. The role of pharmaceutical care, defined by Hepler and Strand2 as “the responsible provision of drug therapy for the purpose of achieving definite outcomes that improve the patient’s quality of life” has been rapidly extended. In this context pharmaceutical care could be considered as similar to pharmacotherapy follow-up3. However, other approaches have been made, such as medicines management, medication review, or more general like cognitive pharmacy services, which are not dissimilar concepts but introduce notable discrepancies in the terminology.